(untitled) (Jurnal Elektronika dan Telekomunikasi, 2022)
The temperature validation controlled by temperature indication has a vital role in the polymerase chain reaction (PCR) test machine or thermal cycler. However, the validation process is complicated for several types of thermal cycler. Some PCR test machines must close the lid tightly while running. It makes the probe’s cable of the temperature sensor might be pinched or break when the thermal cycler lid is closed. Opening the lid (open-air condition) makes the measurement will not accurate. To solve this problem, wireless temperature measurement and validation methods for PCR machines are developed based on magnetic field measurements. The magnetic field of the object will respond to any changes in temperature. The hall-effect sensor, which is validated by gauss meter, detects any magnetic response a certain material covers even the object. This detection yields output data processed to find the thermal cycler’s appropriate temperature wireless validation method. The experiment used a Neodymium magnet as a wireless probe. The position of the Neodymium magnet pole significantly affected the relation between magnetic flux and temperature in experimental results. The reversed pole toward sensors had better linearity (R2= 0.8062) than the unreversed pole (R2= 0.7794). The annealing step commonly achieved the optimum measurement uncertainty. However, the measurement uncertainty and signal sensitivity investigation recommended employing the beneficial combination of pole magnet position to design the temperature validator based on magnetic induction for a closed lid thermal cycler (PCR machine). Overall, the experimental yields can be used to build a wireless temperature validator for a sealed PCR machine based on magnetic induction.